Kajian Pengembangan Petani Berbasis Modal Sosial (Studi Kasus pada Kelompok Tani Lubek Manis Kecamatan Tanjung Palas Tengah Kabupaten Bulungan) - Zulhafandi Zulhafandi; Haris Munandar; Nia Kurniasih Suryana; Mohammad Wahyu Agang; Hery Bachrizal Tanjung (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
Social capital has an essential impact on the development of social and economic aspects of society, especially farmers, who are the dominant profession in rural communities. Among the social capital that exists in society are relationships between individuals, social networks, trust, norms, participation, and cooperation. The purpose of this study is to identify internal and external factors and formulate a strategy for developing social capital-based farmer groups in Salimbatu Village, Tanjung Palas Tengah District, Bulungan Regency. The sample determination method used was purposive sampling, and the respondents in this study were 15 farmers as informants and three as key informants who were members of the Lubek Manis farmer group. The analysis used in this study is a SWOT Analysis (Strength, Weakness, Opportunity, Threat). Internal factors in the development of social capital-based farmer groups have a total strength score of 3.83. At the same time, the weakness has a total score of 3.12. At the same time, external factors in the form of opportunities have a total score of 3.56. At the same time, the threat has a total score of 3.30. Based on the SWOT analysis, aggressive strategies in the development of farmer groups are obtained, namely Increasing the frequency of counseling activities in the Lubek Manis farmer group, Establishing cooperation with several farmer groups, and Increasing mutual trust among members.